2013
DOI: 10.1007/s12032-013-0482-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA-E gene polymorphism on HLA-E expression in tumor cells and prognosis in patients with stage III colorectal cancer

Abstract: Human leukocyte antigen (HLA)-E can contribute to the escape of cancer cells from host immune mechanisms. However, it is unknown whether HLA-E gene polymorphisms might play a role in cancer immune escape. This study aimed to evaluate the correlation between HLA-E gene polymorphisms and HLA-E expression in tumor tissue and determine the effects on clinical outcome of patients with stage III colorectal cancer. Two hundred thirty patients with stage III colorectal cancer were enrolled. HLA-E expression was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Bossard et al (12) revealed that the HLA-E expressed in colorectal cancer cells may combine with the HLA-E receptor CD94/NKG2A expressed on the surface of CTL and NK cells, which contributed to the inhibition of the activity of the CTL and NK cells. Zhen et al (21) hypothesized that the overexpression of HLA-E in colorectal cancer cells was often associated with lower long-term disease-free survival rate and poor prognosis. Levy et al (13) demonstrated that HLA-E expression on the surface of colorectal cancer cell membranes could inhibit the cetuximab-mediated antibody-dependent cell-mediated cytotoxicity, which may promote the immune evasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bossard et al (12) revealed that the HLA-E expressed in colorectal cancer cells may combine with the HLA-E receptor CD94/NKG2A expressed on the surface of CTL and NK cells, which contributed to the inhibition of the activity of the CTL and NK cells. Zhen et al (21) hypothesized that the overexpression of HLA-E in colorectal cancer cells was often associated with lower long-term disease-free survival rate and poor prognosis. Levy et al (13) demonstrated that HLA-E expression on the surface of colorectal cancer cell membranes could inhibit the cetuximab-mediated antibody-dependent cell-mediated cytotoxicity, which may promote the immune evasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…in laryngeal carcinoma [14], mammary carcinoma [15], small cell lung cancer [16], pancreatic cancer [17] ovarian carcinoma [11] and in colorectal carcinoma [18, 19]. Concerning hematopoietic malignancies HLA-E surface expression was found in a high percentage of lymphoid tumor cells and was associated with a protection from NK cell-mediated cytotoxicity [20].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-HLA-E monoclonal antibody 3H2679 (Santa Cruz, USA) was used. HLA-E expression was evaluated as described previously [5]. …”
Section: Methodsmentioning
confidence: 99%
“…In the major mechanism underlying tumor immune escape, HLA-E binds to the leading peptides of HLA-A, -B, -C, and -G, activating the CD94/NKG2A receptor and delivering an inhibitory signal to NK and CTL cells [3]. Studies have found that HLA-E is highly expressed in a variety of tumors [4] and closely associated with certain biological characteristics of tumors [5]. However, HLA-E expression in NB tissue and its clinical significance is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%